Letter: impact of Epstein‐Barr virus serological status on clinical outcomes in adult patients with inflammatory bowel disease. Issue 4 (28th January 2019) - Ahmed, Tehmina; Brown, Francesca; Ahmed, Ruhina; Shah, Ash; Whitehead, Simon; Steed, Helen; Brookes, Matthew J.
Abstract : Linked Content This article is linked to de Francisco et al and de Francisco et al papers. To view these articles, visit https://doi.org/10.1111/apt.14933 and https://doi.org/10.1111/apt.15125 .